ナンキョク ジンコウ ジシン カンソク ヨウ ペネトレーター ノ カイハツ (2) 1990 ネンド ケイカ ホウコク - 渋谷, 和雄; シブヤ, カズオ; 神沼, 克伊; カミヌマ, カツタダ; 早川, 雅彦; ハヤカワ, マサヒコ; 藤村, 彰夫; フジムラ, アキオ; 塚本, 茂樹; ツカモト, シゲキ; 水谷, 仁; ミズタニ, ヒトシ; et al. (1992)
P(論文) ヘリコプターのGPS differential positioningによるペネトレーターの位置決定実験を北海道石狩郡当別町の町営青山牧場で行った。Differentialの固定点はセールロンダーネ実験を想定して200km南西の函館に設置した。160-1000mの対地高度でホバリングしているヘリコプターから6回の自由落下による投下試験を行った。投下ペネトレーターの着地位置をGPS干渉測位法で0.1m精度で定め, ヘリコプターのリアルタイム航法位置から推定される着地位置の精度を調べた。その結果, ペネトレーターを切り離す瞬間を含む前後について各々10-20秒程度(1秒間隔)のヘリコプター飛行軌跡が得られれば, ペネトレーターの落下飛跡による着地位置推定精度は30m, 落下点直上で約1分間ホバリングできれば10m精度が確保できることがわかった。一方, differential法によるヘリコプターの高さ精度はほぼ±10mだった。ただし, differentialの基準点座標を単に基準点に設置した受信器のpoint positioning結果の時間平均値で固定すると, その平均値が持つ±10mの高さ誤差がさらに加算され, リアルタイム位置の高さ精度は±20mに劣化した。また, 対地速度20km/h以下, 対地高度200m以上のヘリコプターからペネトレーターを自由落下させれば, 貫入姿勢が垂直から±5°以内の傾きで停止することも確かめられた。 GPS differential positioning test on the Antarctic penetrator was made at the Aoyama Pasture, Ishikari-Tobetsu-machi, Hokkaido. The reference GPS receiving site was chosen in Hakodate, 200km southwest of the Aoyama Pasture, taking the planned operation on the SΦr Rondane Mountains 400km profile in Antarctica into consideration. Three dummy penetrators were dropped twice by changing the release height in the range 160-1000m above the ground. Six impact positions of the deployed penetrators were determined by a relative carrier phase measurement to an accuracy of 0.1m, and the position results were compared with the post-processed GPS differential positions. When 10-20s duration GPS position data could be acquired at an interval of 1s before and after the release instance (1s accuracy to UTC) of the penetrator, the estimated impact position by tracing the falling trajectory was found to be within 30m offset from the actual impact location determined by the relative carrier phase measurement. When the GPS hovering data could be acquired for at least 1 minute duration just above the impact crater, the calculated impact location via the hovering-helicopter GPS position data was found to be within 10m offset from the actual impact location. The height accuracy of GPS differential positioning was ±10m (PDOP=5-20), which is considered to degrade to ±20m when the coordinates of the reference GPS ...